Novel hydrophilic and hydrophobic amorphous silica: Characterization and adsorption of aqueous phase organic compounds - Andrea Luca Tasca; Farnaz Ghajeri; Ashleigh J Fletcher (Adsorption Science & Technology, 2018)
Very few studies have investigated the adsorption performance of hydrophobic and hydrophilic silicas with dissolved organics in water, which is a required final step during produced water treatment. The cost of functionalization also hinders the use of hydrophobic materials as sorbents. Novel hydrophilic silicas, prepared at low temperature and ambient pressure, were characterised by SEM, FTIR and BET analysis, and studied for the adsorption of aqueous phase organic compounds at concentrations below their solubility limits. Adsorption capacities were found to be up to 264 mg/g for benzene and 78.8 mg/g for toluene. Direct comparison is made with the analogous hydrophobic version of one of the silica materials, demonstrating comparable uptakes for benzene concentrations lower than 50 mg/L. This finding supports the hypothesis that, at very low aqueous phase organic concentrations, hydrophobicization has no discernible effect on access of the pollutants to the internal porosity of the material.